Different β nucleants and the resultant microstructural, fracture, and tensile properties for filled and unfilled ISO polypropylene. Issue 1 (11th July 2012) - Varley, Russell J.; Dell'Olio, Mel; Yuan, Qiang; Khor, Sarah; Leong, K. H.; Bateman, Stuart
Abstract This article explores the use of two β nucleants to improve the fracture behavior of filled and unfilled homo‐polypropylene (PP). The first was based upon an organic quinacridone, whereas the second was based upon the inorganic calcium pimelate. Formulations containing various concentrations of nucleant were prepared using single screw extrusion and then characterized by X‐ray diffraction, differential scanning calorimetry (DSC), Izod impact strength, and tensile testing. The quinacridone nucleating agent produced higher levels of β crystallinity and better improvement in strain to failure, whereas the calcium pimelate imparted greater improvement in impact strength regardless of whether the PP was filled or unfilled. No direct relationship between β crystallinity and fracture properties was observed though synergistic enhancement in impact strength was evident. By varying the concentration of calcium carbonate in the calcium pimelate from 10 : 1, 5 : 1, 2 : 1, and 1 : 1 weight composition of calcium carbonate to pimelic acid, similar property enhancements were achieved regardless of composition although the 10 : 1 sample did produce superior elongation to break. The importance of cooling rate on microstructure within each sample was explored via a through the thickness study using DSC and nano‐indenting methods. Variations in the β content through the thickness were related to cooling and found to be independent of sample composition and processing. Elastic properties varied inversely with β content. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013